An average-value model of kinematic Stirling engine for the study of variable-speed operations of dish-stirling solar-thermal generating system - Li, Y.; Choi, San Shing; Yang, C. (2014)
A simplified model of the Stirling engine is developed for the study of grid-connected variable-speed operations of dish-Stirling (DS) solar-thermal power plant. The model relates the average values of the engine state variables and also takes into account engine losses, the variations of heater temperature and total mass of the working gas in the engine cylinder. The improved model is compared with the existing models and the new model is shown to be more suitable for grid-related studies and control system design. © 2014 IEEE.